RESULTS OF A TRAINING COURSE FOR CALCULATION OF THE MODIFIED RODNAN SKIN SCORE IN SCLERODERMA - Can, Gercek; Avsar, Aydan Koken; Kocaer, Sinem Burcu; Kenar, Gokce; Solmaz, Dilek; Yarkan-Tugsal, Handan; Birlik, Merih (Bmj Publishing Group, 2019)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 12-15, 2019 -- Madrid, SPAIN